Absolute music, mechanical reproduction - Ashby, Arved Mark (University of California Press, 2010)
Recordings are now the primary way we hear classical music, especially the more abstract styles of "absolute" instrumental music. In this original, provocative book, Arved Ashby argues that recording technology has transformed our understanding of art music. Contesting the laments of nostalgic critics, Ashby sees recordings as socially progressive and instruments of a musical vernacular, but also finds that recording and absolute music actually involve similar notions of removing sound from context. He takes stock of technology's impact on classical music, addressing the questions at the heart.